Tres perspectivas sobre lo humano en Arquíloco y Simónides - Jeria S., Patricio (Byzantion Nea Hellás, 2015)
It could be said that Archilochos and Simonides are the opposite ends of a process of artistic, social and politic transformation that began in VII century b. C. and decanted, at last, in the golden age of greek culture. This writting propose a comparation, by means of analysis on some fragments, of Archilochos and Simonides views about three topics: virtue, bravery and human existence. Both poets positioned themselves, in relation to their own comunities, as exceptionals men, for this reason their fragments show an acute critique to ideologies wich were predominant in their respective times. This results in the reafirmation of personal points of view as principles to judge reality, moreover it is outstanding the optimism and serenity with wich both artists assume the consequences of their poetic andintelectual reflextion about individual and social human phenomenon.